2022
DOI: 10.3390/jcm11020286
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Control of the FreeStyle Libre System in the Pediatric Population with Type 1 Diabetes Dependent on Sensor Adherence

Abstract: Aims: To evaluate the relationship between daily sensor scan rates and changes in HbA1c and hypoglycemia in children. Methods: We enrolled 145 paediatric T1D patients into a prospective, interventional study of the impact of the FreeStyle Libre 1 system on measures of glycemic control. Results: HbA1c was higher at lower scan rates, and decreased as the scan rate increased to 15–20 scans, after which it rose at higher scan rates. An analysis of the change in hypoglycemia, based on the number of daily sensor sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…A recent study on children and adolescents with T1D using isCGM showed a U-shaped relationship between daily numbers of scans count and change in glycemic control. In this study, too, the optimum number of isCGM scans was 15–20 per day [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study on children and adolescents with T1D using isCGM showed a U-shaped relationship between daily numbers of scans count and change in glycemic control. In this study, too, the optimum number of isCGM scans was 15–20 per day [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Three types of CGM systems are currently available: real-time CGM (rtCGM), intermittently viewed CGM (ivCGM), and intermittently scanned CGM (isCGM) [ 7 ], which were used in this study. The isCGM system provides the same type of glucose data measured with rtCGM but requires the user to purposely scan the sensor to obtain information and does not have alerts and alarms [ 8 ]. Numerous studies show that flash glucose monitoring is associated with significant improvements in HbA1c in adults and children with T1DM [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The FGM system has been proved in the Al Hayek's prospective study to improve clinical parameters once the patients had been switched from the fingerprick method to FGM over 12 weeks in children and teenagers with T1D ( 10 ). Moreover, a recent study demonstrated a significant and sustained reduction in HbA1c over 6 months in a pediatric population with FGM ( 11 ). However, none of those studies have alternated the use of FGM with SMBG.…”
Section: Introductionmentioning
confidence: 99%